Optimization of Outpatient Service Schedule at Type C Hospital - Nurahmadi, Fauzan (Cattleya Darmaya Fortuna, 2025)
Outpatient services in Type C hospitals often encounter scheduling inefficiencies due to limited human and infrastructural resources. This study proposes a scheduling optimization approach using Integer Programming to allocate doctors optimally across various clinics. The aim is to minimize patient waiting time and enhance the operational efficiency of medical personnel. The model is implemented using Python and the PuLP library, and tested with data from a Type C hospital in North Sumatra. Simulation results indicate that this approach can reduce patient waiting times by up to 25% and ensure a more equitable distribution of workloads.